Editorial [Hot Topic: The Impact of the G-Quadruplex Conformation in the Development of Novel Therapeutic and Diagnostic Agents Executive (Guest Editor: Stefano Alcaro)] - Alcaro, Stefano (Current Pharmaceutical Design, 2012)
The anticancer pharmacological treatment is typically affected by a non optimized therapeutic index. In the last decade several novel molecular targets have been identified and when possible used to design innovative anticancer agents. Among them a special fold of the DNA, known as G-quadruplex conformation, has been found particularly attractive for some important reasons. Firstly, it is exclusive of guanine-rich DNA sequences that are able to create, due to the formation of Hoogsteen hydrogen bonds, a structural core different from the most common Watson and Crick double helix. Secondly, it is expressed especially in the telomeric regions of the genome undergoing undefined repeating sequence in correlation with uncontrolled cell proliferation. Thirdly, some oncogenes and promoters, such as c-kit, myc, contain the sequence prerequisites to fold into a G-quadruplex conformation. On the basis of these considerations, an emergent approach for innovative anticancer agents is based on the stabilization of this conformation via the identification of ligands that are able to selectively bind it. Moreover, in 2009 the Nobel prize for Medicine has been assigned to three scientists that discovered the role of telomers and telomerases confirming this research area as an “hot topic” in the anticancer field. In this special issue international experts with multidisciplinary competencies contribute to highlight the G-quadruplex impact in the development of novel therapeutic and diagnostic agents. A general description about occurrence and genomic location of this special DNA conformation is introduced by Paeschke and coworkers [1]. In the scientific community the DNA G-quadruplex conformational polymorphism is one of the major disputed topic, treated by Alcaro and co-workers by docking simulations using as probes both enantiomers of the most active natural compound telomestatin [2]. Finding out ligands that are able to recognize the G-quadruplex core of specific DNA sequences is a new goal for the modern medicinal chemists. The state-of-the-art in the currently available methodologies is described by the research groups of Randazzo [3] and Jaumot [4].....